In educating students in the spirit of national pride Using the heritage of Termez scholars - Toshpolatova Matluba Kholiyorovna (Peerian Journals Publishing, 2022)
The article examines the way of life and legacy of the Great Termezis, who lived and created the younger generation on our land, studied their knowledge and advice in educating the younger generation, as well as the upbringing, spiritual and moral views and recommendations of the Termezis.
Keywords: scholars; education; upbringing; heritage